Inhibition of clot formation in deterministic lateral displacement arrays for processing large volumes of blood for rare cell capture. Issue 10 (21st May 2015) - D'Silva, Joseph; Austin, Robert H.; Sturm, James C.
<x xml:space="preserve">Abstract</x> Disabling of mechanisms driving clot formation in deterministic lateral displacement arrays allows rare cell capture from large volumes of blood.